Effects of Xinjierkang on Nrf2/HO-1 expression in viral myocarditis mice models - Yin, Jie; Li, Wencheng; Yao, Weidong (Cellular and Molecular Biology, 2020)
In this study, the changes of Nrf2/HO-1 and cytokines TNF-Î±, IL-6, IL-17 and IL-1Î² in cardiac muscle cells of Viral myocarditis (VMC) mice were detected in order to clarify the mechanism of action of Xinjierkang (XJEK). One hundred and fifty healthy male BALBC mice were randomly divided into the normal group, model group, low-, medium- and high-dose XJEK groups, with 30 in each group. Replication of the VMC model in mice inoculated with CVB3m. Serum inflammatory factors TNF-Î±, IL-6, IL-17 and IL-1Î², Nrf2 and HO-1 protein levels in myocardial tissue were compared. The results showed that no apoptotic cells were found in the myocardium of normal mice. The percentage of cardiomyocyte apoptosis in the low, medium and high dose groups of XJEK was significantly lower than the model group (P <0.05). At 3, 7, 14, 21, and 28 days after inoculation, compared with the normal group, the TNF-Î±, IL-6, IL-17 and IL-1Î² levels in the model group significantly increased (p < 0.05). After the administration of XJEK, compared with the model group, the TNF-Î±, IL-6, IL-17, and IL-1Î² levels in the low-, middle-, and high-dose XJEK groups significantly decreased (p < 0.05). At 28 days after inoculation, compared with the normal group, the expressions of Nrf2 and HO-1 proteins in the myocardial tissue of the model group were significantly down-regulated (p < 0.05); and compared with the model group, the expressions of Nrf2 and HO-1 proteins in the low-, medium-, and high-dose XJEK groups were significantly up-regulated (p < 0.05) in a concentration-dependent manner. In conclusion, XJEK can prevent myocardial injury in VMC mice, and its mechanism of action may be related to improving myocardial cell apoptosis, inhibiting inflammatory response, and up-regulating the expression of Nrf2 and HO-1 proteins in myocardial tissue.